Indonesian migrant workers in the framework of legal protection and business existence - Ibrahim, Maulana; Dalimunthe, Reja; Wulandari, Poppy (Privietlab, 2025)
This study discusses legal protection for Indonesian migrant workers in the dynamics of the diaspora and public policy challenges. Indonesian Migrant Workers play an important role as contributors to the country’s foreign exchange, but still face various problems such as human rights violations, violence, exploitation, and weak legal protection in the destination country. This study uses a descriptive qualitative approach with a juridical-sociological method through in-depth interviews and participatory observation of Indonesian migrant workers and secondary data analysis from official government documents and international reports. The results of the study show a significant gap between the protection policies that have been set by the government and the reality of their implementation in the field. The main problems include the rampant non-procedural placement by illegal agents, low digital literacy of Indonesian migrant workers regarding the government’s online reporting system, and limited coordination between related institutions. This study highlights the importance of cross-sector collaboration, both state and private, and the use of information technology to strengthen complaint mechanisms and the supervision of migrant worker placement in a transparent and accountable manner.